PENGEMBANGAN DIFUSI INOVASI DALAM PENDIDIKAN: Konsep, Model, dan Implementasi di Era Digital - Susilawati, Susilawati; Susanti, Rahmi; Maharani , Siti dewi; Anwar, Yenny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article examines in depth the development of the diffusion of innovation within the context of education. Diffusion of innovation is the process by which new ideas or practices are spread through certain communication channels within a social system over time. The diffusion of innovation theory developed by Everett M. Rogers serves as the primary foundation of this study, complemented by perspectives from other scholars in education and educational technology. This article discusses the basic concepts of diffusion of innovation, its key elements, categories of adopters, models of diffusion development, factors influencing the success of diffusion, as well as the challenges and opportunities of innovation diffusion in the digital era. The method used is a literature review (library research) with a descriptive-analytical approach. The findings indicate that the success of educational innovation diffusion largely depends on the interaction between the characteristics of the innovation, the quality of communication channels, the role of change agents, and the condition of the social system. In the digital era, social media and online learning platforms significantly accelerate the diffusion process; however, they do not always ensure deep and sustainable adoption.